Cardiac Vagal Index Does Not Explain Age-Independent Maximal Heart Rate - Duarte, C. V.; Araujo, C. G. (International Journal of Sports Medicine, 2013)
Cardiac vagal tone (CVT), a key determinant of resting heart rate (HR), is progressively withdrawn with incremental exercise and nearly abolished at maximal effort. While maximal HR decreases with age, there remains a large interindividual variability of results for any given age. In the present study, we hypothesized that CVT does not contribute to age-independent maximal HR. Data were obtained from 1 000 (39±14 years old) healthy subjects (719 men) who were not taking medications affecting CVT or maximal HR performed a clinically normal and truly maximal cardiopulmonary exercise testing. CVT was estimated using the cardiac vagal index (CVI), a dimensionless ratio obtained by dividing 2 cardiac cycle durations – end of exercise and pre-exercise -, reflecting HR increases during a 4-s unloaded cycling test (a vagally-mediated response). Maximal HR was expressed as % of that predicted by age (208–0.7 × age (years)). Linear regression analyses identified that CVI can explain only 1% of the % age-predicted maximal HR variability with a high standard error of estimate (~6.3%), indicating the absence of a true physiological cause-effect relationship. In conclusion, the influence of CVI on % of age-predicted maximal HR is null in healthy subjects, suggesting distinct physiological mechanisms and potential clinical complementary role for these exercise-related variables.
Keywords: Parasympathetic; cardiopulmonary exercise testing; 4-s exercise test; healthy subjects